Comparison of the Effectiveness of Sexual Education and Sensory, Proprioceptive, and Tactile Exercises on Children's Anxiety - Safarnia, Mahdieh; Estaki, Mahnaz; Salehi, Mahdieh (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to compare the effectiveness of sexual education and sensory, proprioceptive, and tactile exercises in reducing anxiety in children aged 4 to 7 years. Methods and Materials: This quasi-experimental study used a pre-test and post-test design with a control group. A sample of 30 children, aged 4 to 7 years, was selected from five clinics in Tehran using convenience sampling. The participants were randomly assigned to two experimental groups (10 participants each) and one control group (10 participants). The research tools included the Sensory Integration Evaluation Form by Ryz, the Spence Children’s Anxiety Scale, a sexual education training package for parents, and a sensory integration exercise package for the children. Data were analyzed using two-way repeated measures analysis of covariance (ANCOVA), with Greenhouse-Geisser and Huynh-Feldt adjustments due to violations of the sphericity assumption. Findings: The findings revealed significant reductions in anxiety for both experimental groups compared to the control group. The sensory, proprioceptive, and tactile exercises group demonstrated the most substantial reduction in anxiety, particularly in generalized anxiety, social phobia, obsessive-compulsive tendencies, and separation anxiety. In the sexual education group, anxiety also decreased significantly, especially in social phobia and separation anxiety. The control group did not show significant changes in anxiety levels across the study's three phases (pre-test, post-test, follow-up). Conclusion: Both sensory-based interventions and sexual education significantly reduced anxiety in children, with sensory, proprioceptive, and tactile exercises showing the most pronounced effects. These findings support the use of multi-modal approaches for anxiety reduction in children and suggest that both interventions could be effectively integrated into therapeutic and educational practices.